2021
DOI: 10.1016/j.psj.2021.101400
|View full text |Cite
|
Sign up to set email alerts
|

Feeding live Black Soldier Fly larvae (Hermetia illucens) to laying hens: effects on feed consumption, hen health, hen behavior, and egg quality

Abstract: The use of insects in animal feed has the potential to reduce the demand for soybean production and reduce the deforestation and loss of natural resources. In particular, the black soldier fly ( BSF , Hermetia illucens ) larvae have received attention due to their ability to convert organic waste into high-value biomass. Several studies have investigated the effects of providing BSF larvae to both broilers and laying hens. However, knowledge gaps regarding hens’ vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…Similar results were reported by Wallace et al (2018) for pre-slaughter body weight, eviscerated percentage, heart, liver and giblet yield in guinea fowls and Loponte et al (2017) for eviscerated percentage, heart yield and liver yield in Partridge. Contrary to these findings, significantly (p<0.05) higher pre-slaughter body weight was reported by Tahamtani et al (2021) (Tahamtani et al, 2021). The lower abdominal fat percentage of the birds fed with BSFL in the present study could be due to positively charged chitosan which has the ability to combine with fatty acids, other lipids and bile acids and prevent their absorption through intestine and also by preventing lipid emulsification (Ylitalo et al, 2002).…”
Section: Resultscontrasting
confidence: 85%
“…Similar results were reported by Wallace et al (2018) for pre-slaughter body weight, eviscerated percentage, heart, liver and giblet yield in guinea fowls and Loponte et al (2017) for eviscerated percentage, heart yield and liver yield in Partridge. Contrary to these findings, significantly (p<0.05) higher pre-slaughter body weight was reported by Tahamtani et al (2021) (Tahamtani et al, 2021). The lower abdominal fat percentage of the birds fed with BSFL in the present study could be due to positively charged chitosan which has the ability to combine with fatty acids, other lipids and bile acids and prevent their absorption through intestine and also by preventing lipid emulsification (Ylitalo et al, 2002).…”
Section: Resultscontrasting
confidence: 85%
“…Chickens are excellent foragers of insects as these are among their natural feed sources ( Star et al, 2020 ). Feeding experiments indicated that diets containing insects are highly interesting for poultry species ( Moula et al, 2018 ; Nascimento Filho et al, 2020 ; Star et al, 2020 ; Tahamtani et al, 2021 ). The use of whole BSFL as feed for poultry may be particularly important in organic farming and low-input systems (e.g., local farming with less feed processing and transportation), and where insect production could be integrated into production cycles (e.g., insects farming with locally available organic residues as feed substrate) ( Nyakeri et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inclusion of 5 and 10% live BSFL in broiler rations increased activity and improved leg health without adverse effects on broiler performance ( Ipema et al, 2020b ; Bellezza Oddon et al, 2021 ). Recently, Tahamtani et al (2021) fed laying hens with 0, 10, 20% of the daily DM intake or ad libitum with live BSFL and found no difference in BW of hens given BSFL up to 20%, whereas ad libitum BSFL fed hens were heavier and consumed more protein, fat and energy than control hens. However, there are no data to show how a proportion of more than 10% whole BSFL in broiler rations affects acceptance, nutrient intakes, bird performance and health.…”
Section: Introductionmentioning
confidence: 99%
“…The so-obtained insect larvae are, indeed, predominantly fractionated to obtain meals and oils, which can efficiently be utilized to replace the conventional protein and lipid sources in monogastric diets ( Ravi et al, 2020 ). However, the scientific research recently carried on revealed that insect live larvae may also potentially reach an interesting market share in the form of environmental enrichments for either poultry ( Pichova et al, 2016 ; Veldkamp and van Niekerk, 2019 ; Ipema et al, 2020 ; Star et al, 2020 ; Bellezza Oddon et al, 2021 ; Tahamtani et al, 2021 ) or pigs ( Ipema et al, 2021a ; Ipema et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Welfare assessment in broiler chickens is usually object of a multiperspective approach, as heterogeneous parameters (such as plumage status, hock burns and footpad dermatitis, lameness, behavioural patterns, and excreta corticosterone) are commonly evaluated ( Weimer et al, 2018 ; Giersberg et al, 2021 ; Iannetti et al, 2021 ; Lourenço da Silva et al, 2021 ). Despite beneficial live insect larvae-related effects on bird behaviour and feathering scores having recently been highlighted in either turkeys ( Veldkamp and van Niekerk, 2019 ) or laying hens ( Star et al, 2020 ; Tahamtani et al, 2021 ), data about modulation of plumage status and excreta corticosterone in broiler chickens reared in live insect larvae-enriched environment are still missing. Furthermore, no studies assessing the effects of the concomitant administration of BSF and YM live larvae as environmental enrichments are currently available in poultry.…”
Section: Introductionmentioning
confidence: 99%